Constraints in Adoption of Beekeeping as an Enterprise in Nagaland - A. K. Singh , Rudra P. Singh and Namrata Singh, (Indian Journal of Extension Education, 2016)
Present study was envisaged and accomplished in order to know the constraints of beekeeping adoption by trainedpeasantry. Hundred beekeepers were randomly selected and their opinion was obtained by administering a questionnaire.The key economic constraints of beekeeping adoption were complications in finance from banks, commencement costinvestment beyond the capacity of trained peasantry and lack of government subsidy in apiculture. The relevance of newtechnology, lack of adequate scientific knowledge and inclination towards traditional beekeeping were also constraints ofbeekeeping adoption. The socio- psychological constraints unfurled by beekeeping adoption were fear of high risk, fear ofsting in beekeeping and perceived low outcome. All respondents realized honey price is very low but about customerreliance their doctrine was divisible; majority of respondents broached positively about customer reliance on honeywhereas few faced problem for selling honey.